Transfer Intergovernmental dan Disiplin Fiskal Pemerintah Daerah: Tinjauan Sistematis Moral Hazard dalam Sistem Desentralisasi Fiskal - Kisma Dian; Rina Tjandra Kirana (Jurnal Akuntansi Keuangan Dan Perpajakan | E-ISSN : 3063-8208, 2026)
Fiscal decentralization grants regional governments broader authority in managing regional finances and development. However, the large allocation of intergovernmental transfers from the central government often creates fiscal dependency, potentially weakening disciplined regional financial management. This situation raises indications of moral hazard, where regional governments tend to be less than optimal in generating Regional Original Revenue (PAD) and increasing the efficiency of public spending. This study used a Systematic Literature Review (SLR) approach, referring to the PRISMA 2020 guidelines, to synthesize various empirical findings related to the relationship between fiscal transfers and regional government fiscal behavior. The results of the literature synthesis indicate that the dominance of transfer funds contributes to low fiscal independence, increased budget dependency, and weak incentives to increase regional revenue capacity. Therefore, a more performance-based and accountability-based transfer policy design is needed to strengthen fiscal discipline and promote sustainable regional financial management within a fiscal decentralization framework.